PENGARUH PARTISIPASI PENGANGGARAN PADA KINERJA MANAJERIAL - Mia Sulistiari Putri, Ni Putu; Wijana Asmara Putra, I Nyoman (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
Budgeting participation considereded as an approach that can improve the effectiveness of the company's budget, which will improve managerial performance. Several studies that examined the relationship between budgetary participation and managerial performance showed inconsistent results. This study aims to examine the effect of budgeting participation on managerial performance through budget adequacy, budget goal commitment, organizational commitment, and motivation, on the star hotel in Denpasar. Samples determined with census techniques and data were analyzed using path analysis. Results showed that budgeting participation affect on managerial performance, and their relationship also affected by budget adequacy, budget goal commitment, organizational commitment, and motivation.
Keywords: budgetary participation, managerial performance, budget adequacy, budget goal commitment, organizational commitment, work motivation